Gut microbiota and autoimmune thyroid disease: a bidirectional Mendelian randomization study and mediation analysis - Fang, Yiqiao; Zhang, Xinyue; Huang, Rui; Liu, Jiaye; Li, Zhihui (Frontiers in Microbiology, 2024)
The gut microbiota (GM) plays a pivotal role in influencing various health outcomes, including immune-mediated conditions, but its potential association with autoimmune thyroid disease (AITD) remains underexplored. We aimed to investigate the potentially pathogenic or protective causal impacts of specific GM on two types of AITD, namely Graves' disease and Hashimoto's thyroiditis, and analyzed the mediating effect of 731 immune cell phenotypes.Methods: Leveraging pooled genome-wide association study (GWAS) data of 211 gut microbiota traits, 731 immune cell phenotypes, and two types of AITD (Hashimoto's thyroiditis and Graves' disease), we performed bidirectional Mendelian randomization (MR) analyses to explore the causal relationships between the GM and AITD. Subsequently, we employed a multivariable MR analysis to discover potential mediating immune cell traits.Additionally, sensitivity analyses were utilized to ensure the reliability of the outcomes.Results: Our analysis revealed that a total of 7 GM taxa were positively associated with AITD, and other 14 taxa showed a negative correlation with AITD. Furthermore, we identified several immune cell traits that mediated the effects of GM on AITD. Most notably, Actinobacteria (p) presented protective effects on Hashimoto's thyroiditis via CCR2 on myeloid Dendritic Cell (5.0%), and Bifidobacterium (g) showed facilitating effects on Graves' disease through CD39+ CD4+ T cell %CD4+ T cell (5.0%) and CD14 on CD33+ HLA DR+ CD14dim (12.2%).The current MR study provides evidence supporting the causal relationships between several specific GM taxa and AITD, and further identified potential mediating immunophenotypes.